Human potential and its influence on the development of the China economy - Nadiia Kazakova; Alina Sholom; Shi Huili (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2022)
Traditional sources of national power of the countries of the world are currently much less important in ensuring the high competitive status of national economies than such factors as the presence of a powerful innovative potential of states, the speed of their mastering the scientific and technological model of economic development and, most importantly, the quality of human resources and conditions of its reproduction. The subject of the study is the conditions and factors of human resource development of national economies and its impact on the development of the economy of the People’s Republic of China. The goal is to assess the level of development of the economies of the world’s regions depending on the state of human potential. as well as detection. The objective: to reveal the research methodology of the "human resource" category, to analyze the impact of human resources on the development of the country’s economy, to assess the current state of the human resources of the PRC and to substantiate the main directions of development and qualitative improvement of the country’s human resources. Methods: historical-logical method (when studying the category "human resource" and classifying theories revealing its content, as well as revealing the evolution of the formation and development of the world and domestic scientific school of human resource research); system-structural analysis of economic processes and phenomena (when studying processes of transnationalization of human resources at the micro, state, regional, and global levels); analysis and synthesis (when studying modern forms of intellectualization of production in social reproduction, clarifying the role of human resources in the formation of strategic competitive advantages of countries and the impact of investments in human resources on indicators of the intellectual and educational and qualification level of the population); the method of quantitative and qualitative comparisons (when assessing the qualitative and quantitative characteristics of the human resources of the People’s Republic of China according to international criteria of its competitiveness); statistical and graphic methods (when processing and summarizing statistical data and displaying them in the most informative form - tables, figures, diagrams). The following results were obtained: methodological approaches to the definition of the "human resource" category were revealed, the evolution of the human factor in the process of socio-economic and humanitarian transformations of global development was studied, and the relationship between human resources and the development of the Chinese economy was determined. Conclusions: it is calculated that human potential is of decisive importance for the economic development of the PRC, investing in human potential and promoting its development, in particular through foreign economic cooperation in the field of higher education, turn into the most effective type of investment that contributes to economic growth.